Sociodemographic Determinants Affecting the Practice of Breast Self-Examination Among Women in Northern Ghana - Oteng, Joseph (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Cancer is a group of diseases in which genetically damaged cells proliferate autonomously. Such cells cannot respond to normal regulatory mechanisms that ensure the intercellular cooperation required in multicellular organisms. Consequently, they continue to proliferate, thereby robbing nearby normal cells of nutrients and eventually crowding surrounding healthy tissue. Breast cancer is the most widespread malignancy among females worldwide, accounting for the greatest percentage of deaths (15.5%) from all cancers in women. It was estimated the number of new cases in 2020 would exceed 2.2 million. The research work showed that the participants were abreast with Breast self-examination (BSE) techniques. And that majority of our respondents have a significantly positive impression of BSE. This tallies with the outcome of a study on affected perception of BSE among female secondary school teachers with high perception of BSE. Regarding age, there is a noticeable trend regarding the increase in age and the mean age. Specifically, women aged 30-39 years have the highest mean BSE practice score (41.8947), followed by those aged 40-49 years (40.3333), while the lowest mean score is observed among women aged 10-19 years (36.0000). This suggests a potential correlation between age and BSE practice, with older women exhibiting higher BSE engagement. In conclusion this study's primary objective is to assess the practice and determinants of breast self-examination among women in Chereponi District, Northern Region of Ghana. It will help other part of the world to create awareness of the importance of Breast cancer examination at the early stage, avoiding complication in feature.